Lucidone inhibits autophagy and MDR1 via HMGB1/RAGE/PI3K/Akt signaling pathway in pancreatic cancer cells - Chen, Sheng‐Yi; Hsu, Yi‐Hao; Wang, Sheng‐Yang; Chen, Ying‐Yin; Hong, Cheng‐Jie; Yen, Gow‐Chin (Phytotherapy research, 2022)
Gemcitabine (GEM) drug resistance remains a difficult challenge in pancreatic ductal adenocarcinoma (PDAC) treatment. Therefore, identifying a safe and effective treatment strategy for PDAC is urgent. Lucidone is a natural compound extracted from the fruits of Lindera erythrocarpa Makino. However, the role of lucidone in PDAC inhibition remains unclear. In addition, high‐mobility group box 1 (HMGB1) and receptor for advanced glycation end products (RAGE) are involved in multidrug resistance protein 1 (MDR1) regulation and GEM resistance. Thus, this study aimed to explore the function of lucidone in tumor cytotoxicity and chemosensitivity through the suppression of RAGE‐initiated signaling in PDAC cells. The data showed that lucidone significantly promoted apoptotic cell death and inhibited the expression of autophagic proteins (Atg5, Beclin‐1, LC3‐II, and Vps34) and MDR1 by inhibiting the HMGB1/RAGE/PI3K/Akt axis in both MIA Paca‐2 cells and MIA Paca‐2GEMR cells (GEM‐resistant cells). Notably, convincing data were also obtained in experiments involving RAGE‐specific siRNA transfection. In addition, remarkable cell proliferation was observed after treatment with lucidone combined with GEM, particularly in MIA Paca‐2GEMR cells, indicating that lucidone treatment enhanced chemosensitivity. Collectively, this study provided the underlying mechanism by which lucidone treatment inhibited HMGB1/RAGE‐initiated PI3K/Akt/MDR1 signaling and consequently enhanced chemosensitivity in PDAC.